A comparative analysis of a novel flow field pattern with different channel size configurations - Hazar, Hanbey; Yilmaz, Mustafa; Sevinc, Huseyin (Elsevier Sci Ltd, 2022)
Flow field styles in PEM (proton exchange membrane) fuel cells are crucial for cell performance. An enhanced flow field provides more homogenous reactant diffusion in the cell, lower pressure drop, and higher electrical performance. A unique flow field design was designed in this study and the design was tried to be enhanced by varying the channel dimensions of the design. For this purpose, seven flow field models were analyzed by the ANSYS program using the computational fluid dynamics (CFD) technique as three-dimensional and single-cell. The flow areas were prepared with an active area of 50 cm(2) and channel widths of 1, 1.5, and 2 mm. The polarisation curve, pressure drops, pressure, temperature, and O-2 and H2O mass distribution were all considered while evaluating the results. The study revealed that the geometric dimensions of the flow channels had a substantial impact on the chemical reactions and electrical characteristics of the cell. The M1 model with the highest net power density was built and experimentally tested based on the simulation results. According to the analytical results, the M1 model exhibited a maximum net power density of 0.498 W/cm(2) at 0.4 V. The M0 and M1 models demonstrated higher temperature values and diffusion area on the catalyst surface compared to the other models. More reaction activity in the flow field resulted from spreading the mass distribution as widely as possible on the catalyst surfaces. The experimental and numerical I-V curves of the M1 model showed a high similarity.
Keywords: Fuel cell; PEMFC; Flow field pattern; Computational fluid dynamic (CFD); Performance